Livability and sustainability of urbanism. An interdisciplinary study on history and theory of urban settlement. - Wiryomartono, Bagoes (Palgrave Macmillan, 2020)
This book is a wide-reaching interdisciplinary examination of urbanism in the context of humanities and social sciences research, comprising cutting-edge theoretical and empirical investigations of urban livability and sustainability. Urban livability is explored as a phenomenon of happenings that gather people, things, and domains in the specific spatiotemporal context of the city; this context is the life-world of urbanism. Meanwhile, sustainability is conceived of as the capacity of urbanism that enables people to cultivate their sociocultural and economic existence and development without the depletion of their current resources in the future. In this study, phenomenology is uniquely incorporated as a way of seeing things according to their presence in space and time.
Keywords: Stadtforschung; Stadttheorie; Urbanismus; Nachhaltigkeit; Lebensqualität; Siedlungsform; Wohnort; Stadtgesellschaft; Interdisziplinarität; Stadtplanung; Stadtökologie; Internationaler Vergleich; Ontologie; Global City